(untitled) (Research, Society and Development, 2023)
Objective: To describe nursing care for newborns with neonatal jaundice. Methodology: This was an integrative literature review study, with a qualitative and exploratory approach. Data collection took place between January and March 2023 using Bollean descriptors and operators" ’’Hyperbilirubinemia’’ AND "Newborns" AND "Neonatal jaundice" AND "Nursing care" AND "phototherapy". database of the Virtual Health Library (BVS), SciELO, articles published in Portuguese in the period between 2017 and 2022. Results: The selected sample consisted of 16 articles, according to the inclusion and exclusion criteria. of the selected studies showed that the role of the nurse is fundamental, since the main therapeutic line for this pathology is care. Conclusion: The importance of nursing has been understood in supporting newborns affected by jaundice, both in prevention and in the treatment and rehabilitation of -born with this pathology.